1997
DOI: 10.1007/s001670050024
|View full text |Cite
|
Sign up to set email alerts
|

American football injuries in Germany

Abstract: This study investigated the incidence of injury in German Bundesliga football based on the evaluation of two American football teams before and during the season 1995. Certified team physicians and team physiotherapists were the initial medical professionals providing on-site diagnosis, injury documentation and first aid for all injuries. An injury was defined as minor (group I) causing the player to miss practice or game sessions up to 1 week without requiring surgery; as severe (group II) causing the player … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[32, 134,135] Parachuting Fracture (100.0) [138] Roller Skating Fracture (86.5) Sprain (13.5) [142,143] Rollerblading / Inline Skating Fracture (83.3) Sprain (16.7) [ 77,176,179,186,188,190,191,[193][194][195][196]225,226] Soccer (Indoor) Sprain (87.8) [198,199] * Items with weight prevalence percentage smaller than 1.0% are omitted. [60] ) Aeroball 1.37 [61] American Football 0.54-4.15 [55,62,65] , (Game:…”
Section: Resultsmentioning
confidence: 99%
“…[32, 134,135] Parachuting Fracture (100.0) [138] Roller Skating Fracture (86.5) Sprain (13.5) [142,143] Rollerblading / Inline Skating Fracture (83.3) Sprain (16.7) [ 77,176,179,186,188,190,191,[193][194][195][196]225,226] Soccer (Indoor) Sprain (87.8) [198,199] * Items with weight prevalence percentage smaller than 1.0% are omitted. [60] ) Aeroball 1.37 [61] American Football 0.54-4.15 [55,62,65] , (Game:…”
Section: Resultsmentioning
confidence: 99%
“…In youth and professional football, linemen have a threefold increased risk of injury, followed by running backs and Evaluation of the Back-in-Action test Battery In Uninjured High School American Football Players wide receivers, possibly due to frequent involvement in play actions and tackling. 2,[57][58][59][60][61][62] The current measurements reveal impaired results for the above listed position Group 1 including linemen (G1), which were alarmingly even below results of an age matched reference population. Comparably, recent studies have found a correlation between injury risk of the lower extremity and BMI >26 kg/m 2 in high school aged linemen.…”
Section: Functional Tests Reveal Major Deficits In Knee Capability Me...mentioning
confidence: 78%
“…Injury rates are then calculated as the number of injuries per 1,000 hours of sports participation. 3,4,6,7,10,12,14,[27][28][29][30][31][32] This is the unit of risk adopted by many European researchers in sports such as football (soccer) and rugby.…”
Section: Exposurementioning
confidence: 99%
“…2,3 Although many systems are used, sports epidemiologists have reiterated the need for uniform reporting standards and methodologies. 2,[4][5][6][7][8][9][10][11][12][13][14] Dance medicine researchers have echoed this call for a uniform standard. [15][16][17] The dance community may learn from discussions among sports medicine researchers about injury surveillance.…”
mentioning
confidence: 99%
See 1 more Smart Citation